CDBA-Based Universal Biquad Filter and Quadrature Oscillator - Worapong Tangsrirat; Tattaya Pukkalanun; Wanlop Surakampontorn (My University, 2008)
The voltage-mode universal biquadratic filter and sinusoidal quadrature oscillator based on the use of current differencing buffered amplifiers (CDBAs) as active components have been proposed in this paper. All the proposed configurations employ only two CDBAs and six passive components. The first proposed CDBA-based biquad configuration can realize all the standard types of the biquadratic functions, that is, lowpass, bandpass, highpass, bandstop, and allpass, from the same topology, and can also provide orthogonal tuning of the natural angular frequency(ωo)and the bandwidth (BW) through separate virtually grounded passive components. By slight modification of the first proposed configuration, the new CDBA-based sinusoidal quadrature oscillator is easily obtained. The oscillation condition and the oscillation frequency are independently adjustable by different virtually grounded resistors. The sensitivity analysis of all proposed circuit configurations is shown to be low. PSPICE simulations and experimental results based upon commercially available AD844-type CFAs are included, which confirm the workability of the proposed circuits.
Keywords: Digital biquad filter; Quadrature (astronomy); All-pass filter; Oscillation (cell signaling); Analog and Mixed-Signal Circuit Design